Novel Study in Learning History (Descriptive Analytical Study of the Ability of the History Education Department Students in Appreciating Novel) - Fauzi, Wildan Insan (Prodi. Pendidikan Sejarah FPIPS UPI dan APPS (Asosiasi peneliti dan Pendidik Sejarah), 2013)
The background of this study is the writerâ€™s concern about history learning which only focuses on rote learning and textbook that makes the student drown in the sea of facts. Therefore, it is true what Tolstoy said that history is nothing but a useless collection of stories which aimed is only for â€œentertainment.â€ The aim of Novel study can balance the intellectual side and the value of learning, give a better chance to remind various historical facts, and make history learning more enjoyable. However, the history teacherâ€™s ability to appreciate the historical novel needs to support these purposes. The focus of this paper is â€œhow good are the History Education Department students appreciating novels in history learning?â€ This research study used a qualitative approach to find a complex and holistic picture of the studied subject. Besides, the researcher also uses the phenomenology approach, which is used to understand how the students sense their experience when studying the novel and use it to observe the perception, ideas, imagination, emotion, desire, willingness, and action they showed when they analyzed the historical novel.